Radiographic and CT appearance of cavitary pulmonary lesions in a lamb. Issue 12 (15th September 2021) - Kan, J; Bauquier, J; Tyrrell, D; O'Byrne, K; Stent, AW; Brosnan, B
Abstract : Background: Pulmonary abscesses may be cavitary lesions on thoracic radiographs and computed tomography (CT). Case report: A 26‐day‐old, cross‐breed lamb presented for respiratory distress despite procaine penicillin treatment. Thoracic radiographs revealed several pulmonary ovoid thin‐walled gas and soft tissue opacity structures. CT showed that these gas‐filled structures enclosed mildly contrast enhancing soft tissue attenuating material and surrounded the lobar bronchus to the right middle and caudal lung lobes. Imaging revealed pulmonary cavitary lesions, and chronic pulmonary abscesses was confirmed with histopathology on samples obtained from a right caudal lung lobectomy. Conclusion: To the authors' knowledge, this is the first radiographic and CT report of cavitary pulmonary lesions in a lamb. The pulmonary abscesses in this case were suspected to be due aspiration pneumonia occurring during bottle feeding, along with the high possibility of failure of passive transfer from its orphan history.